2013
DOI: 10.2166/wst.2013.352
|View full text |Cite
|
Sign up to set email alerts
|

Management and treatment of landfill leachate by a system of constructed wetlands and ponds in Singapore

Abstract: Lorong Halus, Singapore's first landfill leachate treatment system, consists of a pre-treatment system (8,000 m(2)), five constructed reed beds (38,000 m(2)), five polishing ponds (13,000 m(2)), an education centre and a learning trail for visitors. Eight species of wetland plants (total 160,000 plants) were selected for their ability to uptake nutrients, tolerance to low phosphorus concentrations and resistance to pest infestations. The wetland was launched in March 2011 and water quality monitoring started i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The reported removal efficiency showed a varied range of treatment across various CW applications. A study of CW to treat landfill leachate by experimental systems showed a significant BOD5 removal efficiency between 91% and 96% of total nitrogen (TN), as reported by Sim et al [6]. Meanwhile, a wetland system in Australia-Townsville achieved a slightly lower range (48-67%) of BOD 5 removal, similar to another project, which consisted of four linear channels where a reduction efficiency of about 46% was reported [37].…”
Section: Case Studies On Constructed Wetlands For Wastewater Treatmen...supporting
confidence: 59%
See 2 more Smart Citations
“…The reported removal efficiency showed a varied range of treatment across various CW applications. A study of CW to treat landfill leachate by experimental systems showed a significant BOD5 removal efficiency between 91% and 96% of total nitrogen (TN), as reported by Sim et al [6]. Meanwhile, a wetland system in Australia-Townsville achieved a slightly lower range (48-67%) of BOD 5 removal, similar to another project, which consisted of four linear channels where a reduction efficiency of about 46% was reported [37].…”
Section: Case Studies On Constructed Wetlands For Wastewater Treatmen...supporting
confidence: 59%
“…Constructed wetlands (CWs) are fast-growing wastewater treatment technologies designed and constructed to simulate actual physical, chemical and biological processes occurring in natural wetlands [4]. They are manmade wetlands designed to operate and mimic natural wetlands using vegetation, soil and microorganisms, and they may appear as Land 2022, 11, 1388 2 of 17 a more ecologically endowed system for wastewater treatment as either a new or restored habitat for native and migratory wildlife [5,6]. The proven advantages in utilizing the CWs for wastewater treatment as green and sustainable technology was discussed by many researchers and resulted in tremendous increases in both research and applications as a result of the simultaneous rise in the environmental sensitivity [3,7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Constructed wetlands are considered to be a sustainable passive wastewater treatment technology, and have been used to treat a variety of wastewaters for decades, including domestic or municipal wastewater [1,2], industrial wastewater [3,4], agricultural [5][6][7], acid mine drainage [8], river and lake water [9][10][11], groundwater [12], landfill leachate [13][14][15], highway [16] and airport [17] runoff. They take advantage of many of the same processes that occur in natural wetlands, but do so in a more controlled or engineered system [18].…”
Section: Introductionmentioning
confidence: 99%
“… 61 Inland lakes can emit significant amounts of methane from sediment layers, equivalent to 20% of fossil fuel emissions. 73 Our study site, which is next to a historic landfill, 74 could have nutrient-rich sediments releasing methane sources to MOB. The archaeal community in the anoxic sediment layer is believed to be the exclusive source of methane production from lakes.…”
Section: Discussionmentioning
confidence: 99%